Report of the Sub-Group on "Environment" for 12th Five Year Plan (Dated October 2011) - Planning Commission (Planning Commission, 2011)
With the increasing emphasis on need for development, coupled with increasing urbanization, it is becoming apparent that the natural resources are to be used judiciously and sustainably. Increasing instances of - cities violating air pollution norms, rivers and other water bodies getting polluted due to discharge of untreated sewage and industrial wastewater, indiscriminate disposal of solid waste causing degradation and pollution of land - are source of concern both of the health of human and ecology. In addition to pollution of ambient air, the pollution of indoor air especially due to use of biomass for cooking in rural and semi-urban households is a matter of concern because of its adverse health impacts faced by most vulnerable section of society - women and small children. These issues are therefore needed to be addressed in timely and inclusive manner.
Ministry of Environment and Forests, Government of India